Development of introductory teaching materials for the collaborative science laboratory of culture, Islam and technology - Suryandari Suryandari; Meyninda Destiara; Helda Rahmawati (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The development of introductory teaching materials for the collaborative science of culture, Islam, and technology is research that produces innovative teaching materials as references for introductory laboratory courses and similar subjects. This study aims to develop teaching materials and validate products by material experts and media experts. The development of teaching materials is carried out in stages: (1) enrichment of teaching materials by laboratory introductory materials in the curriculum of biology, physics, and chemistry study programs, (2) collecting local potential data that can be included and explained in teaching materials according to laboratory introductory materials, (3) explore information related to Islam-science according to the phenomena presented, (4) innovate material content by presenting 3D augmented reality technology which has explained the use and installation of supporting applications, (5) validate teaching materials on material and media aspects, (6) implement teaching materials in the introductory laboratory learning process and or laboratory management in physics, chemistry and biology study programs. This development research stage is in line with the ADDIE model development research. The validation results obtained a percentage of 79% for material experts and 88% for media experts who both belong to the "strongly agree" category to be suitable for use by revising.Abstrak Pengembangan bahan ajar pengantar laboratorium sains kolaborasi budaya, islam dan teknologi merupakan penelitian yang menghasilkan produk bahan ajar inovatif sebagai referensi mata kuliah pengantar laboratorium dan mata kuliah sejenisnya. Penelitian ini bertujuan untuk mengembangkan bahan ajar dan menvalidaasi produk oleh ahli materi dan ahli media. Pengembangan bahan ajar dilakukan dengan tahapan: (1) pengayaan materi ajar sesuai dengan materi pengantar laboratorium pada kurikulum program studi tadris biologi, fisika dan kimia, (2) mengumpulkan data potensi local yang dapat dicantumkan dan dijelaskan pada bahan ajar menyesuaikan materi pengantar laboratorium, (3) menggali infomasi berkenaan dengan islam-sains sesuai pada fenomena yang disajikan, (4) melakukan inovasi konten materi dengan menyajikan tenologi augmentedr reality 3D yang telah dijelaskan penggunaan dan pemasangan aplikasi pendukung, (5) melakukan validasi bahan ajar pada aspek materi dan media, (6) mengimplementasikan bahan ajar dalam proses pembelajaran pengantar laboratorium dan atau manajemen laboratorium pada program studi tadris fisika, kimia dan biologi. Tahapan penelitian pengembangan ini selaras dengan penelitian pengembangan model ADDIE. Hasil validasi diperoleh persentase 79% pada ahli materi dan 88% pada ahli media yang sama-sama termasuk pada ketegori “sangat setuju” untuk layak digunakan dengan melakukan revisi.